A systematic review and meta‐analysis comparing second‐generation cryoballoon and contact force radiofrequency ablation for initial ablation of paroxysmal and persistent atrial fibrillation. (23rd July 2020) - Ravi, Venkatesh; Poudyal, Abhushan; Pulipati, Priyanjali; Larsen, Timothy; Krishnan, Kousik; Trohman, Richard G.; Sharma, Parikshit S.; Huang, Henry D.
Abstract: Introduction: Cryoballoon ablation (CBA) and radiofrequency ablation (RFA) are the preferred modalities for catheter ablation of atrial fibrillation (AF). Technological advances have improved procedural outcomes, warranting an updated comparison. We sought to evaluate the efficacy and safety of CBA–2nd generation (CBA‐2G) in comparison to RFA‐contact force (RFA‐CF) in patients with AF. Methods: MEDLINE, Cochrane, and ClinicalTrials.gov databases were searched until 03/01/2020 for relevant studies comparing CBA‐2G versus RFA‐CF in patients undergoing initial catheter ablation for AF. Results: A total of 17 studies, involving 11 793 patients were included. There was no difference between the two groups in the outcomes of freedom from atrial arrhythmia ( p  = .67) and total procedural complications ( p  = .65). There was a higher incidence of phrenic nerve palsy in CBA‐2G (odds ratio: 10.7; 95% confidence interval [CI]: 5.85 to 19.55;  p  < .001). Procedure duration was shorter (mean difference: −31.32 min; 95% CI: −40.73 to −21.92; p  < .001) and fluoroscopy duration was longer (+3.21 min; 95% CI: 1.09 to 5.33; p  = .003) in CBA‐2G compared to RFA‐CF. In the subgroup analyses of patients with persistent AF and >1 freeze lesion delivered per vein, there was no difference in freedom from atrial arrhythmia. Conclusions: In AF patients undergoing initial ablation, CBA‐2G and RFA‐CF were equally efficacious. The procedure duration was shorter, but with a higher incidence of phrenic nerve palsy in CBA‐2G. In patients with persistent AF, there was no difference in the efficacy between CBA‐2G or RFA‐CF techniques.